2018
DOI: 10.1097/hcr.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Low-Volume Time-Efficient Resistance Training Versus Endurance Training in Patients With Heart Failure

Abstract: These results demonstrate that AMC and TRE equally improved exercise capacity and health-related quality of life in lower New York Heart Association-stage HF patients, despite less time required as well as lower energy expenditure during TRE than during AMC. Therefore, TRE might represent a time-efficient exercise modality for improving adherence to exercise in patients with class I-II HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…In this study, the walked distance was just below 400 meters in both groups at baseline, which is in line with similar studies (95). They increased their walked distance by about 100 meters, which was statistically significant, and more than average in similar studies (95)(96)(97). There were no significant differences regarding training effects between the 2 groups that received an initial period of hospital-based training or not.…”
Section: Exercise Trainingsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the walked distance was just below 400 meters in both groups at baseline, which is in line with similar studies (95). They increased their walked distance by about 100 meters, which was statistically significant, and more than average in similar studies (95)(96)(97). There were no significant differences regarding training effects between the 2 groups that received an initial period of hospital-based training or not.…”
Section: Exercise Trainingsupporting
confidence: 90%
“…In recent years, attempts to streamline exercise training with shorter bouts of exercise have been made, e.g. aerobic interval training (AIT) with higher intensity (143) or low-volume time-efficient resistance training (96). Wisloff et al (143) showed that AIT on treadmill with as high as 95% of peak HR in older patients with HF (76.5±9 years) was well tolerated compared with moderate continuous walking at an intensity of 70-75% of peak HR.…”
Section: Life-long Training Programmementioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the neuromuscular system is associated with increased motor units and increased firing frequency. Previous studies reported that resistance exercise, even at low intensity, improves exercise tolerance [ 19 ]. The improvement in physical function with resistance training in the early phase is considered to be a result of neural adaptations and may be associated with an increase in motor units [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding assessment characteristics, all the included studies (100%) assessed endothelial function (38-58) and seven (33%) also measured vascular smooth muscle function (40,41,43,(46)(47)(48)57). Fourteen studies (67%) measured endothelial function in the brachial artery (38-42, 44, 47-49, 53, 55-58), four (19%) in the radial artery (45,46,51,54), one (5%) in the femoral artery (52), and two (9%) in the brachial artery and lower limb arteries (i.e., femoral and posterior tibial) (43,50). Eleven studies (52%) placed the cuff distal to the appraised artery (38, 40-44, 46, 47, 49, 53, 56), ve (24%) proximal (45,51,54,55,58), and one (5%) positioned the cuff distal to the brachial artery and proximal to the posterior tibial artery (50), while four (19%) did not speci cally disclose this information (39, 48, 52, 57) and guidelines for measuring FMD were referenced (14,59).…”
Section: ***Insertmentioning
confidence: 99%